Factors determination MOOCs continuance intention: a proposed conceptual framework - Nur Shamsiah, Abdul Rahman; N S, Wan Zainal Adli; Anis Farihan, Mat Raffei; Nor Syahidatul Nadiah, Ismail (IOP Publishing, 2020)
In recent years, Massive Open Online Courses (MOOCs) is start to gain its popularity at most universities and the number of MOOC has increased. Despite its popularity, previous study shown that low course completion rate and limited amount of studies to examine factors that influence students’ continuance intention to use MOOCs. Thus, this study aims to propose a conceptual framework to evaluate the factors determinant of MOOCs continuance intention among higher education students. By reviewing the related studies, factors namely perceived ease of use, perceived usefulness, attitude, motivation and continuance intention were identified.